Робастная адаптивная идентификация нестационарных временных рядов с помощью ансамбля обучаемых гибридных адаптивных моделей - Бодянский, Е.В.; Винокурова, Е.А.; Кобылин, И.О.; Мулеса, П.П. (Управляющие системы и машины, 2016)
Предложены модели робастной адаптивной идентификации нестационарных временных рядов в on-line режиме поступления потока данных, характеризующиеся простотой вычислительной реализации. Проведен ряд имитационных экспериментов на основе тестовых и реальных данных. Запропоновано моделі робастної адаптивної ідентифікації нестаціонарних часових рядів в on-line режимі надходження потоку даних, що характеризуються простотою обчислювальною реалізації. Проведено низку імітаційних експериментів на основі тестових і реальних даних. Computationally simple and high-speed adaptive algorithms for robust identification of nonstationary non-linear time series are proposed. The distinctive feature of such algorithms is an ability to implement them using the learning models, which are consisted of the elementary arithmetic operations. The possibility of on-line information processing provides a solution of a wide class of problems, which are appeared in Data Stream Mining tasks. Also an ensemble of tuning hybrid adaptive models is proposed. This system allows to choose the best model in the context of accepted quality criterion at each discreet instant of time.